Lectins from Edible Mushrooms - Senjam Singh; Hexiang Wang; Yau Sang Chan; Wenliang Pan; Xiuli Dan; Cui Yin; Ouafae Akkouh; Tzi Bun Ng (2014)
Mushrooms are famous for their nutritional and medicinal values and also for the diversity of bioactive compounds they contain including lectins. The present review is an attempt to summarize and discuss data available on molecular weights, structures, biological properties, N-terminal sequences and possible applications of lectins from edible mushrooms. It further aims to update and discuss/examine the recent advancements in the study of these lectins regarding their structures, functions, and exploitable properties. A detailed tabling of all the available data for N-terminal sequences of these lectins is also presented here.